Crusted scabies in remote Australia, a new way forward: lessons and outcomes from the East Arnhem Scabies Control Program. Issue 11 (16th June 2014) - Lokuge, Buddhi; Kopczynski, Alex; Woltmann, Angela; Alvoen, Faye; Connors, Christine; Guyula, Terrence; Mulholland, Eddie; Cran, Samantha; Foster, Tim; Lokuge, Kamalini; Burke, Tanya; Prince, Sam
Summary: Crusted scabies is a highly infectious, debilitating and disfiguring disease, and remote Aboriginal communities of northern Australia have the highest reported rates of the condition in the world. We draw on monitoring data of the East Arnhem Scabies Control Program to discuss outcomes and lessons learnt through managing the condition in remote communities. Using active case finding, we identified seven patients with crusted scabies in three communities and found most had not presented to health services despite active disease. We compared presentations and hospitalisations for a cumulative total of 99 months during a novel preventive program with 99 months immediately before the program for the seven cases and seven sentinel household contacts. Our preventive long‐term case management approach was associated with a significant 44% reduction in episodes of recurrent crusted scabies (from 36 to 20; P = 0.025) in the seven cases, and a non‐significant 80% reduction in days spent in hospital (from 173 to 35; P = 0.09). It was also associated with a significant 75% reduction in scabies‐related presentations (from 28 to 7; P = 0.017) for the seven sentinel household contacts. We recommend active surveillance and wider adoption of this preventive case management approach, with ongoing evaluation to refine protocols and improve efficiency. Contacts of children presenting with recurrent scabies should be examined to exclude crusted scabies. In households where crusted scabies is present, a diagnosis of parental neglect due to recurrent scabies and weight loss in children should be made with extreme caution. Improved coordination of care by health services, and research and development of new therapies including immunotherapies for crusted scabies, must be a priority.